1999
DOI: 10.1590/s0100-204x1999000800011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization for plant height and flowering date in the biological species oat

Abstract: The use of wild oat races in artificial hybridization with cultivated oat (Avena sativa L.) has been used as a way of increasing the variability. This work aimed to identify the variability for plant height and flowering date of groups of cultivated oat genotypes, wild introductions of A. fatua L. and segregating populations of natural crosses between A. sativa and A. fatua. Wide genetic variability was observed for both traits in the groups and between them. The wild group of A. fatua L. showed high plants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…The PS in this study ranged from 70 cm to 130 cm, and interestingly, the similar values have been reported by Brazilian research group [27].…”
Section: Anovasupporting
confidence: 91%
“…The PS in this study ranged from 70 cm to 130 cm, and interestingly, the similar values have been reported by Brazilian research group [27].…”
Section: Anovasupporting
confidence: 91%
“…The plant height values of the population mostly ranged from 92.7 to 112 cm. Baltenberger and Frey (1987), Dumlupinar et al (2012a) and Matiello et al (1999) also reported genetic influence for PH. Many reports in the literature indicated that there were high variations among cultivars and years (Ahmad et al 2008;Buerstmayr et al 2007;Dumlupinar et al 2012a;Gautam et al 2006;Ma et al 2006;Nawaz et al 2004;Zaman et al 2006).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Buerstmayr et al (2007), Dumlupinar et al. (2012a), Locatelli et al (2008), Matiello et al (1999) and Nawaz et al (2004) determined genetic influence for VP and earliness. It was also indicated that VP was influenced by environmental conditions (Gautam et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…[33] who reported similar plant height values during their experiment in 1994 in Brazil. Higher oat plant height values were reported for the wild and early maturing group of oat in Brazil [33]. Plant height is a trait strongly related to plant lodging and yield.…”
Section: Oat Plant Heightmentioning
confidence: 67%